Solvent-free oxidation of aldehydes to acids by TBHP using environmental-friendly -exchanged Mg-Al hydrotalcite catalyst - Choudhary, Vasant R.; Dumbre, Deepa K.; Narkhede, Vijay S. (Journal of Chemical Sciences, 2012)
A number of hydrotalcite (Mg-Al, Mn-Al, Co-Al, Ni-Al, Mg-Fe, Mg-Cr and Cu-Al) catalysts, with or without MnO-exchange, were evaluated for their performance in the solvent-free oxidation of benzaldehyde to benzoic acid by tert-butyl hydroperoxide under reflux in the absence of any solvent. The MnO-exchanged Mg-Al-hydrotalcite (Mg/Al = 10) showed high activity in the oxidation of different aromatic and aliphatic aldehydes to their corresponding acids and also showed excellent reusability in the oxidation process which is environmental-friendly.
Keywords: acid; Aldehyde; MnO4-1-exchanged Mg-Al-hydrotalcite catalyst; Oxidation; TBHP